Using real life problems for developing prospective teachers’ classroom management skills - (:unkn) unknown (My University, 2012)
0

The purpose of the present study is to try out an education program designed in accordance with a problem based learning (PBL) approach in a classroom management (CM) lesson and to determine student opinion on the exercise. An action research method was applied in the present research. The exercise was conducted in the fall term of the 2010-2011 academic year. The study group was composed of prospective teachers from six branches of the Atatürk Faculty of Education, Marmara University. For the program design, firstly the topics of the CM lesson were determined and learning goals were created. Then, scenarios including the problems concerning CM were developed. The subjects were learned through the solutions found for these problems. In the research, open-ended questions were used as the data collecting instrument. According to the answers, the prospective teachers found this exercise more useful than other way of presentation since it offered more lasting learning; it offered the opportunity to learn by experience; it was enjoyable and motivating as well as being student oriented. The prospective teachers stated that they learned well the problems presented by the groups and the solutions for them; they felt themselves to be more competent in terms of CM; and they would be able to find solutions should they encounter similar problems in the future. Consequently, it can be said that the PBL approach can be used with the aim of developing CM skills in prospective teachers.
Keywords: Eğitim, Eğitim Araştırmaları